2017
DOI: 10.1093/schbul/sbx130
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Layer Abnormalities as Biomarkers of Schizophrenia

Abstract: Our novel findings demonstrate considerable retinal layer abnormalities in schizophrenia that are related to clinical features and visual function. With time, SD-OCT could provide easily-measurable biomarkers to facilitate clinical assessment and further our understanding of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
47
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 43 publications
(56 reference statements)
5
47
1
Order By: Relevance
“…40 One study found significant thinning of the nasal parafoveal RNFL in SZ compared to HC, but not in the overall or temporal region. 41 While our meta-analysis consisted of a mix of acutely and chronically impaired patients recruited from both inpatient and outpatient settings, we did not identify an effect of disease duration on RNFL thickness. We could not perform a meta-regression of acute vs chronic states since many of the studies combined acute and chronic course.…”
Section: Rnfl Findingsmentioning
confidence: 88%
“…40 One study found significant thinning of the nasal parafoveal RNFL in SZ compared to HC, but not in the overall or temporal region. 41 While our meta-analysis consisted of a mix of acutely and chronically impaired patients recruited from both inpatient and outpatient settings, we did not identify an effect of disease duration on RNFL thickness. We could not perform a meta-regression of acute vs chronic states since many of the studies combined acute and chronic course.…”
Section: Rnfl Findingsmentioning
confidence: 88%
“…Significant inverse correlations have been reported between duration of disease and thickness of the RNFL, temporal parafoveal ISL and temporal parafoveal ONL, as well as macular thinning and volume. 61,62 These correlations with macula thickness and volume suggest progressive neurodegeneration seen in parallel with MRI changes of grey matter volume loss. 123 However, studies containing similar numbers of patients and controls have reported no significant correlation between RNFL thickness or macular thickness with duration of illness.…”
Section: Severity and Duration Of Schizophreniamentioning
confidence: 91%
“…Macular thinning and reduced MV are another reported, yet debated, finding in patients with schizophrenia compared with age-matched controls. Whereas several studies observed overall macular thinning in patients compared with age-matched controls, 61,62,75,79,80 one study observed macular thinning isolated to the nasal and inferior outer macular regions. 81 In contrast, Silverstein and colleagues reported no difference in macular thinning between schizophrenia patients and age-matched controls.…”
Section: Oct In Schizophreniamentioning
confidence: 97%
See 2 more Smart Citations